IMMUNOHISTOCHEMICAL EXPRESSION OF MYELOID CELL LEUKEMIA-1 AND ITS CORRELATION WITH ER, PR, HER 2-NEU +/- CASES OF CARCINOMA BREAST - Dr. Shilpi Patel, Dr. Nishi Tandon, Dr. Andleeb Zehra, Dr. Farheen Khan, Dr. Sharique Ahmad, Dr.NirupmaLal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background & Objectives: Breast carcinoma, the foremost typical cancer and fatal causeamong women worldwide, is marked by unrestrained growth of breast epithelial cells.It’sprognosis depends on biomarkers including Progesterone Receptor (PR), HER2-neu and Estrogen Receptor (ER). Myeloid cell leukemia